Analisis Kompetensi Profesional Guru Pendidikan Agama Islam dalam Pelaksanaan Evaluasi Pembelajaran di Sekolah Menengah - Ahmad Ubadi; Bai Syifa Qurratul Aini; Fitri Hilmiyati; Enung Nugraha (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Islamic education is a crucial component of the Indonesian education system. This field of study significantly influences student character. Teachers in the Islamic education process need to possess advanced skills in organizing, implementing, and assessing learning. Teachers must first improve the learning process to enhance the learning evaluation system. Cognitive, emotional, and psychomotor components must be included in the assessment of Islamic education. Educational evaluation is also part of the realm of educational technology, which cannot be separated from other domains, such as design, development, utilization, and management. Therefore, when determining evaluation mechanisms, it is important to consider the interrelationships between these domains to achieve optimal learning outcomes.